ΒIII‐tubulin suppression enhances the activity of Amuvatinib to inhibit cell proliferation in c‐Met positive non‐small cell lung cancer cells. (10th August 2022) - Brayford, Simon; Duly, Alastair; Teo, Wee Siang; Dwarte, Tanya; Gonzales‐Aloy, Estrella; Ma, Zerong; McVeigh, Laura; Failes, Timothy W.; Arndt, Greg M.; McCarroll, Joshua A.; Kavallaris, Maria
Abstract: Non‐Small Cell Lung Carcinoma (NSCLC) remains a leading cause of cancer death. Resistance to therapy is a significant problem, highlighting the need to find new ways of sensitising tumour cells to therapeutic agents. βIII‐tubulin is associated with aggressive tumours and chemotherapy resistance in a range of cancers including NSCLC. βIII‐tubulin expression has been shown to impact kinase signalling in NSCLC cells. Here, we sought to exploit this interaction by identifying co‐activity between βIII‐tubulin suppression and small‐molecule kinase inhibitors. To achieve this, a forced‐genetics approach combined with a high‐throughput drug screen was used. We show that activity of the multi‐kinase inhibitor Amuvatinib (MP‐470) is enhanced by βIII‐tubulin suppression in independent NSCLC cell lines. We also show that this compound significantly inhibits cell proliferation among βIII‐tubulin knockdown cells expressing the receptor tyrosine kinase c‐Met. Together, our results highlight that βIII‐tubulin suppression combined with targeting specific receptor tyrosine kinases may represent a novel therapeutic approach for otherwise difficult‐to‐treat lung carcinomas. Abstract : Amuvatinib (MP‐470) inhibits lung cancer cell proliferation following βIII‐tubulin suppression as demonstrated by decreased Ki67 and BrdU‐incorporation using ELISA. These data show that suppressing the survival factor βIII‐tubulin, the activity of Amuvatinib (MP‐470) is enhanced.